College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Section P.4 - Rational Exponents and Radicals - P.4 Exercises - Page 30: 57



Work Step by Step

Using $x=3, y=4, z=-1$ and plugging into the equation, we get: $(9x)^{2/3}+(2y)^{2/3}+z^{2/3}=(9*3)^{2/3}+(2*4)^{2/3}+(-1)^{2/3}=(3^{3})^{2/3}+(2^{3})^{2/3}+(1)^{1/3}=3^{2}+2^{2}+1=9+4+1=14$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.